Surgical treatment of large pheochromocytoma (>6 cm): A 10-year single-center experience - Liang Zhang; Danlei Chen; Yingxian Pang; Xiao Guan; Xiaowen Xu; Cikui Wang; Qiao Xiao; Longfei Liu (Asian Journal of Urology, 2022)
Objective: Clinical practice guidelines recommend open adrenalectomy (OA) for large pheochromocytoma (LPCC) > 6 cm in size. Although laparoscopic adrenalectomy (LA) for the treatment of LPCC has been reported, its role remains unclear. This study aimed to compare the effectiveness of LA and OA, and summary the surgical treatment experience. Methods: Data concerning LPCC, from January 2010 to June 2019 of a single institution, were retrospectively reviewed. Altogether 82 patients with a tumor larger than 6 cm were included (52 patients in LA group and 30 patients in OA group). Groups were balanced by propensity score matching (PSM) into 15 pairs. Patients’ demographics, preoperative characteristics, and prognosis were analyzed. Results: Before PSM, the OA group had larger tumor sizes (median [interquartile range, IQR]: 8.9 [7.3–10.3] vs. 7.2 [6.7–8.0] cm; p=0.000) and higher vanillylmandelic acid level (median [IQR]: 114.3 [67.8–326.4] vs. 66.6 [37.8–145.8] μmol/24 h; p =0.004) and needed a higher cumulative dose of prazosin (median [IQR]: 83.5 [37.0–154.0] vs. 38.0 [21.0–81.0] mg; p=0.028). After PSM, the baseline data showed no significant differences between both groups. The LA group had relatively more stable blood pressure in surgery, with a lower fluctuation of systolic blood pressure (mean±standard deviation [SD]: 70.9±25.1 vs. 107.4±46.2 mmHg, p=0.012) and a lower percentage of hemodynamic instability (46.7% vs. 86.7%, p=0.020). The LA group had shorter postoperative hospital stays (mean±SD: 6.4±2.7 vs. 10.1±3.4 days; p=0.003) than the OA group. Differences regarding metastasis rate (6.7% vs. 0, p=1.000) were not statistically significant between LA and OA groups. The median (IQR) follow-up time of 82 patients was 72.5 (47.0–103.5) months. Binary logistic regression showed that right-side tumors or those >8 cm in size were independent risk factors of OA. Conclusion: LA is a safe, minimally invasive procedure for LPCC and has relatively better perioperative characteristics in large medical centers. Patients with tumors on the right side or larger than 8 cm are more likely to undergo OA initially.